The Effect of Health, Education, and Labor Force with Urban Population as Moderating Variables on Human Development Index in Oic Member Countries - Hasna Fauziana; Ririn Tri Ratnasari (Universitas Airlangga, 2023)
ABSTRACT: This study aims to examine the effect of health, education, and labor force moderated by urban population on the Human Development Index. This study uses a quantitative approach and a Moderated Regression Analysis technique with a sample of 25 OIC countries from 2010-2019 taken by purposive sampling method. The results showed that health, education, and the labor force affected the Human Development Index. While the urban population moderates the effect of health and the workforce on the Human Development Index, the urban population does not moderate the effect of education on the Human Development Index. This study has a novelty in the results of the study, namely the basic education variable which has a significant but negative effect on the Human Development Index. This research is limited to a sample of OIC member countries because more than 30% of poor countries with low income according to World Bank data are in OIC member countries, so it is hoped that this research will be able to provide references related to increasing the human development index to save them from poverty. Keywords: Education, Health, Human Development Index, Labor Force, Urban Population ABSTRAK: Penelitian ini bertujuan untuk menguji pengaruh kesehatan, pendidikan, dan angkatan kerja yang dimoderasi oleh kepadatan populasi terhadap Human Development Index. Penelitian ini menggunakan pendekatan kuantitatif dan teknik Moderated Regression Analysis dengan sampel 25 negara OKI dari tahun 2010-2019 yang diambil dengan metode purposive sampling. Hasil penelitian menunjukkan kesehatan dan angkatan kerja berpengaruh positif signifikan terhadap Human Development Index, namun pendidikan berpengaruh negatif signifikan terhadap Human Development Index. Urban population memoderasi pengaruh antara kesehatan dan angkatan kerja terhadap Human Development Index, namun urban population tidak memoderasi pengaruh pendidikan terhadap Human Development Index. Penelitian ini memiliki kebaruan dalam hasil penelitian, yaitu variabel pendidikan dasar yang justru berpengaruh namun negatif signifikan terhadap Human Development Index. Penelitian ini terbatas dilakukan pada sampel negara anggota OKI sebab lebih dari 30% negara miskin dengan pendapatan rendah menurut Data Bank Dunia adalah ada pada negara anggota OKI, sehingga diharapkan penelitian ini mampu memberikan referensi terkait peningkatan indeks pembangunan manusia untuk menyelamatkannya dari kemiskinan. Kata Kunci: Angkatan Kerja, Human Development Index, Kesehatan, Pendidikan, Urban Population. DAFTAR PUSTAKA Adom, K., & Asare-Yeboa, I. T. (2016). An evaluation of human capital theory and female entrepreneurship in sub-Sahara Africa: Some evidence from Ghana. International Journal of Gender and Entrepreneurship, 8(4), 402–423.doi:10.1108/IJGE-12-2015-0048 Alam, K. (2017). Poverty reduction through enabling factors. World Journal of Science, Technology and Sustainable Development, 14(4), 310–321.doi:10.1108/wjstsd-07-2016-0049 Alkire, S., & Shen, Y. (2017). Exploring multidimensional poverty in China: 2010 to 2014. Research on Economic Inequality, 25, 161–228.doi:10.1108/S1049-258520170000025006 Bakhtiari, S., & Meisami, H. (2010). An empirical investigation of the effects of health and education on income distribution and poverty in Islamic countries. International Journal of Social Economics, 37(4), 293–301.doi:10.1108/03068291011025255 Barkah, T., Rusgianto, S., & Wardhana, A. (2022). Impact of agricultural land and the output of agricultural products moderated with internet users toward the total export of agricultural product in three islamic South East Asian Countries. Media Agribisnis, 6(1).11-22.doi:10.35326/agribisnis.v6i1.2261 Bircher, J., & Kuruvilla, S. (2014). Defining health by addressing individual, social, and environmental determinants: New opportunities for health care and public health. Journal of Public Health Policy, 35(3), 363–386.doi:10.1057/jphp.2014.19 Bradshaw, T. K. (2007). Theories of poverty and anti-poverty programs in community development. Community Development, 38(1), 7–25.doi:10.1080/15575330709490182 Cabus, S., & Stefanik, M. (2019). Good access to adult education and training for the low-educated accelerates economic growth: Evidence from 23 European Countries. KU Leuven HIVA Working Paper Series.1-35.doi:2019/4718/005 Chen, K. M., Leu, C. H., & Wang, T. M. (2019). Measurement and Determinants of Multidimensional Poverty: Evidence from Taiwan. Social Indicators Research, 145(2), 459–478.doi:10.1007/s11205-019-02118-8 Choudhry, M. T., & Elhorst, P. (2018). Female labour force participation and economic development. International Journal of Manpower, 39(7), 896–912.doi:10.1108/IJM-03-2017-0045 Faqihudin, M. (2010). Human development index ( HDI ) salah satu indikator yang populer untuk mengukur kinerja pembangunan manusia. Cermin, 241331(47). Fatima, A., & Sultana, H. (2009). Tracing out the U-shape relationship between female labor force participation rate and economic development for Pakistan. International Journal of Social Economics, 36(1-2), 182–198.doi:10.1108/03068290910921253 Febriyanti, A. R., Ratnasari, R. T., & Wardhana, A. K. (2022). The effect of economic growth, agricultural land, and trade openness moderated by population density on deforestation in OIC countries. Quantitative Economics and Management Studies, 3(2).221-234. Gamlath, S. (2013). The governance dimension of human development. Humanomics, 29(4), 240–259.doi:10.1108/H-03-2013-0015 Gunawan, J., Permatasari, P., & Tilt, C. (2020). Sustainable development goal disclosures: Do they support responsible consumption and production? Journal of Cleaner Production, 246.doi:10.1016/j.jclepro.2019.118989 House, Q. E., Alkire, S., & Santos, M. E. (2010). Acute Multidimensional Poverty: A New Index for Developing Countries. Oxford Department of International Development (OPHI) Working Paper No. 38 Ikenberry, G. J. (2002). Human Development Report 2002:Deepening democracy in a fragmanted world. Foreign Affairs, 81(6).doi:10.2307/20033361 Iman, A. N., Sukmana, R., Ghifara, A. S., & Wardhana, A. K. (2022). The effect of zakat collection, company age, and company's total assets on financial performance of sharia banking in Indonesia 2019-2020. Economic Education and Entrepreneurship Journal, 5(2), 217–224. Jonsdottir, A., & Waghorn, G. (2015). Psychiatric disorders and labour force activity. Mental Health Review Journal, 20(1),13–27.doi:10.1108/MHRJ-05-2014-0018 Mannan, M. A. (1995). Teori dan praktek ekonomi islam. Yogyakarta:Dana Bhakti Wakaf. Mitra, A., & Murayama, M. (2009). Rural to urban migration: A District-Level analysis for India. International Journal of Migration, Health and Social Care, 5(2), 35–52.doi:10.1108/17479894200900011 Oladapo, I. A., & Ab Rahman, A. (2016). Re-counting the determinant factors of human development: a review of the literature. Humanomics, 32(2), 205–226.doi:10.1108/H-02-2016-0018 Pawitro, I. U. (2011). Trend kawasan perkotaan - industri property dan gaya hidup metropolitan. Mercubuana,438–447. Putri, R. M., & Mintaroem, K. (2020). Determinan islamic human development index (IHDI) Provinsi Jawa Timur tahun 2001-2016. Jurnal Ekonomi Syariah Teori Dan Terapan, 6(7), 1410.doi:10.20473/vol6iss20197pp1410-1420 Ryadi, A., & Sincihu, Y. (2013). Indikator sensitif bagi penilaian kualitas hidup manusia